Minat Menggunakan Produk Halal - Muhammad Arfan Harahap (AGHNIYA : Jurnal Ekonomi Islam, 2021)
The use of halal products is a special concern in Islamic teachings, so that interest in using halal products is important for every Muslim. This study aims to find out how the interest in using halal products in STAI-Jama'iyah Mahmudiya Tanjung Pura Langkat students. This type of research is a quantitative research using the analysis approach of Structure Equation Modeling (SEM) based on variance (PLS). WarpPLS 7.0 software was used to help analyze the model and measure the effect of each exogenous variable on the endogenous variable. Where data is collected using questionnaires either directly or online. The results showed that the variable of halal certificate had a significant effect on the variable of interest in using halal products, while the variables of religiosity and halal awareness had a but not significant effect on the variable of interest in using halal products. The joint effect of all exogenous variables on endogenous variables is 0.71%.